APAKAH KEPEMIMPINAN DESTRUKTIF DAN GANGGUAN KESEHATAN MENTAL BERPENGARUH PADA KINERJA KARYAWAN? - Deppi Andam Dewi; Harsono, Mugi (Badan Perencanaan Pembangunan, Riset dan Inovasi Daerah Kabupaten Sragen, 2023)
Mental health issues have not been a serious concern in the workplace, even though mental health disorders in employees cause a decrease in performance. The main trigger of mental health problems comes from leadership factors. However, research on leadership still suffers from a positive bias. This study aims to analyze the role of leadership on mental health and employee performance while examining the moderating role of work autonomy on the relationship between destructive leadership and mental health. This study examined 207 respondents from public sector organizations and then analyzed them using PLS-SEM with the second-order method. The results of this study indicate that destructive leadership has a positive and significant influence on employee mental health problems. However, mental health problems have a positive effect on performance. In addition, autonomy has no moderating effect on the relationship between destructive leadership and mental health. The results of this study can be used by managerial parties to pay attention to the behavior of leaders periodically and prepare appropriate coping strategies to deal with the mental health of their employees, especially in the long term.